Family history of cardiovascular disease and death in patients with out-of-hospital cardiac arrest - Magnus Gylling; Johanna Krøll; Peder Emil Warming; Carolina Malta Hansen; Fredrik Folke; Steen M. Hansen; Lars Køber; Christian Torp-Pedersen; Rodrigue Garcia; Jacob Tfelt-Hansen; Peter E. Weeke (Resuscitation Plus)
Aim: How a family history of cardiovascular disease (CVD) or death influences the risk of out-of-hospital cardiac arrest (OHCA) is unknown. This study examined the prevalence of family histories of CVD and death in patients with OHCA and if these factors were associated with OHCA. Methods: Patients (<70 years) with OHCA’s of presumed cardiac origin and available kinship information were identified from the Danish Cardiac Arrest Register (2001–2014). Patients with OHCA were matched 1:4 (age, sex, and number of identifiable parents) with individuals from the background population (controls) to compare family histories (events in first-degree relatives before OHCA) of CVD, all-cause death, cardiovascular death, and premature death (death <60 years). In conditional multivariable logistic regressions, we examined associations between parental history and offspring OHCA risk. Results: Of 45,293 patients with OHCA 4,994, were eligible for inclusion (median age 50 years at OHCA, 76% male). Of these 47.7% had a family history of CVD (vs. 42.1% of controls), 68.2% of all-cause death (vs. 60.9%), 23% of premature death (vs. 15.8%) and 33.3% of cardiovascular death (vs. 27%) (p < 0.001 for all). A family history of a single parent with CVD (OR: 1.13, 95%CI: 1.05,1.23), all-cause death (OR: 1.42, 95%CI: 1.29,1.56), cardiovascular death (OR: 1.35, 95%CI: 1.24, 1.47), and premature death (OR: 1.45, 95%CI: 1.32,1.59) were all associated with OHCA (p < 0.001 for all). Conclusion: A family history of CVD and death is more common among patients with OHCA compared to a matched background population, as well as being significantly associated with OHCA.